Pembuatan Biokompatibel Suture Anchor Berbasis 3D Printing Filament dari Nano Hidroksiapatit Berbahan Dasar Cangkang Keong Sawah - Zhafira, Tesa Ulima; Berlian, Baskoro David; Karisma, Achmad Dwitama (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Suture anchor is used to attach soft tissues to the bone. One of the materials that can be used for making suture anchors is hydroxyapatite [Ca10(PO4)6(OH)2]. Hydroxyapatite (HAp)  has similarities with the properties of bone minerals, so it has the potential to be used as a material for making biocompatible suture anchors. However, HAp is brittle and has poor strength, so HAp is usually combined with polymers such as composites to overcome the limitations of its mechanical properties. One of the polymers that can be used is Polycaprolactone (PCL). In this study, HAp was synthesized from rice field snail shells, due to its high calcium contents.  Further, the combination of HAp and PCL in the manufacture of 3D printing filaments such as suture anchors was obtained. The variables used in this study were the mixing ratio of HAp:PCL in making filaments with a mixing ratio of 0.5:9.5; 1:9 ; 2:8. The results of various variables shows that the tensile strength most optimal composite in 7,3 % when mixing HAp:PCl is 0.5:9,5.